Turbulence, empowerment and marginalisation in international education governance systems - Taysum, Alison; Arar, Khalid (Bingley, U.K. : Emerald Publishing Limited, 2018)
This book investigates how governance at different levels can improve access to education for excluded communities. It conceptualises turbulence, empowerment, and marginalisation in international educational governance systems, and presents a comparative analysis of five nation states (England, Arabs in Israel, Northern Ireland, Trinidad and Tobago, and the United States). From these carefully-selected case studies, readers are shown how Senior Level Leaders describe turbulence in their systems - and how they articulate both the kind of support they want, and the support they actually get at the infrastructural, resources and agency level. It shows how the Senior Leaders hope to put their track records in school improvement into action in order to mobilise school communities for Empowering Young Societal Innovators for Equity and Renewal. Based on research that is world leading in terms of originality, significance, and rigour, 'Turbulence, Empowerment and Marginalisation in International Education Governance Systems' is both a comprehensive investigation of the question of how systems empower key agents of change in school communities, and a practical guide to how these communities can become societal innovators for equity, peace and renewal.
Prelims -- Part I: Conceptualizing turbulence, empowerment and marginalisation -- Turbulence, empowerment and marginalised groups -- Literature review - turbulence in education governance systems -- Epistemological underpinnings and methodologies for researching marginalised groups in international educational governance systems -- Part II: Five international cases of turbulence, empowerment, and marginalisation -- the turbulence Black, Asian, minority ethnicity chief executive officers of small, medium and empty MATs face in England's education system; the structures -- the turbulence black, Asian, minority ethnicity chief executive officers of small, medium and empty MATs face in England's education system; the agency -- Empowering school principals to overcome turbulence in school partnerships through governance systems for equity, renewal and peace: Northern Ireland -- Supervisors in the Arab education system: between governability, duality and empowerment, through a state of turbulence -- Turbulence in efforts at curriculum renewal for educational equity: a critical analysis of a primary curriculum review exercise in Trinidad and Tobago -- Empowering superintendents in the United States to empower societal innovators for equity and renewal in the community -- Part III: Turbulence, empowerment and marginalisation: knowledge to action -- Turbulence, empowerment, and marginalised groups: a comparative analysis of five international education governance systems -- Conclusions: turbulence, empowerment and marginalised groups -- About the contributors -- Appendix 1 sample invitation letter to interview to the researched -- Appendix 2 -- Appendix 3 -- Appendix 4 -- Appendix 5 -- Appendix 6 -- Index.
Includes index.
Print version record
Keywords: Education -- Administration; Education -- Social aspects; International education; School management and organization; Education -- Administration -- General; Organization & management of education